Functional Characterization of a Missense Variant of MLH1 Identified in Lynch Syndrome Pedigree. (29th January 2020) - Zaib, Tahir; Zhang, Chunhui; Saleem, Komal; Xu, Lidan; Qin, Qian; Wang, Yusi; Ji, Wei; Khan, Hanif; Yu, Hanfei; Zhu, Siqi; Gao, Wei; Huang, Yun; et al.
Abstract : Lynch syndrome (LS) is the most common hereditary colorectal cancer (CRCs) inherited in an autosomal-dominant manner. Here, we reported a multigeneration Chinese family clinically diagnosed with LS according to the Amsterdam II criteria. To identify the underlying causative gene for LS in this family, whole-exome sequencing (WES) was performed. A germline missense variant (c.2054C>T:p.S685F) in exon 18 of MLH1 was successfully identified by WES. Sanger sequencing verified the results of WES and also confirmed the cosegregation of the MLH1 missense variant in all affected members of the family including two unaffected family members. Bioinformatic tools predicted the identified MLH1 variant as deleterious. Immunohistochemistry (IHC) staining showed loss of MLH1 and PMS2 protein expression. In vitro expression analysis also revealed that the identified MLH1 missense variant (c.2054C>T:p.S685F) results in reduced expression of both MLH1 and PMS2 proteins. Based on the American College of Medical Genetics and Genomics (ACMG) guidelines, the missense mutation c.2054C>T in MLH1 was classified as a "pathogenic" variant. Two unaffected family members were later recommended for colonoscopy and other important cancer diagnostic inspections every 1-2 years as both were at higher risk of LS. In conclusion, our findings widen the genotypic spectrum of MLH1 mutations responsible for LS. This study increases the phenotypic spectrum of LS which will certainly help the clinicians in diagnosing LS in multigeneration families. This study also puts emphasis on the importance of genetic counselling for the benefit of asymptomatic carriers of MMR gene variants who are at higher risk of LS.